2009
DOI: 10.1038/bmt.2009.30
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL12-3′A allele is associated with a higher mobilization yield of CD34 progenitors to the peripheral blood of healthy donors for allogeneic transplantation

Abstract: The interaction between CXCL12 and its receptor CXCR4 plays a crucial role in the homing and mobilization of haematopoietic progenitors. We investigated the putative association between a CXCL12 gene polymorphism, the G-A transition at position 801 in the 3 0 -untranslated region (3 0 UTR), and the yield of CD34 þ progenitors in 65 healthy allogeneic transplant donors who received G-CSF. Importantly, in this setting, the analysis was not biased by background disease or chemotherapy. The 3 0 UTR CXCL12 G801A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
2
29
2
Order By: Relevance
“…First evidence of a genetic background determining stem cell mobilization was provided by Benboubker et al [38] who reported an association between the CXCL12-3′A allele and a better mobilization result in healthy stem cell donors. This result could be confirmed by Bogunia-Kubik et al [39] and Ben et al [40]. Martin-Antonio et al [41] reported the same finding and observed associations between mobilization ability and even more polymorphisms, including VCAM-1 und CD44.…”
Section: G-csf Dosing and Factors Affecting Mobilization Efficacysupporting
confidence: 78%
“…First evidence of a genetic background determining stem cell mobilization was provided by Benboubker et al [38] who reported an association between the CXCL12-3′A allele and a better mobilization result in healthy stem cell donors. This result could be confirmed by Bogunia-Kubik et al [39] and Ben et al [40]. Martin-Antonio et al [41] reported the same finding and observed associations between mobilization ability and even more polymorphisms, including VCAM-1 und CD44.…”
Section: G-csf Dosing and Factors Affecting Mobilization Efficacysupporting
confidence: 78%
“…The association of CXCL12-801A with a higher number of G-CSF-mobilized CD34 + cells has been reported in healthy donors 27 and in patients. 28 The CXCL12/CXCR4 interaction plays an important role in the homing of hematopoietic progenitor cells and their egress to PB during situations of stress.…”
Section: Discussionmentioning
confidence: 99%
“…We also report the effect of G-CSF on a genetic variant in CD44 influencing the number of CD34 + cells collected. We note the influence of a genetic variant in CSFR3 on the number of CD34 + cells mobilized by G-CSF, and that the previously reported association of the CXCL12-801A allele with the number of CD34 + cells after G-CSF administration 27 might be due to a dramatic G-CSF-induced decrease in gene expression in donors with this genetic variant. …”
Section: Cd34mentioning
confidence: 95%
“…Genetic polymorphism analyses in humans have identified polymorphisms associated with mobilizing response to G-CSF in untranslated regulatory regions of genes encoding GCSFR, adhesion molecules (VCAM-1, CD44), and chemokines (SDF-1), which are all known to regulate HSC trafficking. 108,109 Genetic polymorphisms may predict for poor mobilization, yet it is premature to apply such screenings in the clinic to identify poor mobilizers prospectively. …”
mentioning
confidence: 99%